Effects of Tai Chi on postural balance and quality of life among the elderly with gait disorders: asystematic review - Xu, Fan; Soh, Kim Geok; Chan, Yoke Mun; Bai, Xiao Rong; Qi, Fengmeng; Deng, Nuannuan (Public Library of Science (PLoS), 2023)
Background Tai Chi is good for improving the physical fitness of older adults. But few studies have reported the effects of Tai Chi on the postural balance and quality of life of older adults with gait disorders.